2012
DOI: 10.1097/sla.0b013e318272de87
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Marker Analysis Allows Risk Assessment for Metastasis in Stage II Colon Cancer

Abstract: MACC1 expression predicts development of metastases, outperforming microsatellite stability status, as well as KRAS/BRAF mutation status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 34 publications
5
66
2
Order By: Relevance
“…Decreased SASH1 mRNA expression was correlated with the occurrence of metachronous distant metastasis, and multivariate analysis identified SASH1 downregulation as an independent negative prognostic parameter for patient survival (Rimkus et al, 2006). Recently, these results were confirmed on an independent patient collective of stage II colon cancer (n=179 patients), confirming that decreased SASH1 expression is an independent negative prognostic factor in colon cancer, allowing to distinguish highrisk patients in early, locally restriced stages of the disease (Nitsche et al, 2012).…”
Section: Notesupporting
confidence: 67%
“…Decreased SASH1 mRNA expression was correlated with the occurrence of metachronous distant metastasis, and multivariate analysis identified SASH1 downregulation as an independent negative prognostic parameter for patient survival (Rimkus et al, 2006). Recently, these results were confirmed on an independent patient collective of stage II colon cancer (n=179 patients), confirming that decreased SASH1 expression is an independent negative prognostic factor in colon cancer, allowing to distinguish highrisk patients in early, locally restriced stages of the disease (Nitsche et al, 2012).…”
Section: Notesupporting
confidence: 67%
“…Recently, SASH1 expression has been linked to a number of diseases such as pre-ecclampsia 149 , Alzheimer disease 150 , colorectal and breast cancer 133,135,136 , skin carcinoma 151 and Dyschromatosis universalis hereditaria (DUH) 141 . While little is known about the role of SASH1 in the vascular physiopathology, an in vitro study has reported SASH1 to be up-regulated following VEGF receptor blockade in human pulmonary microvascular endothelial cells 152 .…”
Section: Discussionmentioning
confidence: 99%
“…The same year SASH1 was used for the first time in a clinical study focusing on the risk assessment of metastasis by biological markers in patients with stage II colon cancer 111 . The study, performed by Nitsche et al on 232 patients, showed that SASH1 expression was decreased in tumor tissues and that low level of SASH1 correlated with decreased survival rate.…”
Section: Sash1 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA of tumor and corresponding normal colon mucosa were extracted and analyzed for microsatellite instability using the Qiagen ® Type-it Microsatellite PCR Kit (Qiagen GmbH, Hilden, Germany), as described before [20] . Following procedures for routine diagnostics, results of PCR analysis were interpreted by an experienced pathologist and were classified into microsatellite stability, low grade microsatellite instability and high grade microsatellite instability.…”
Section: Molecular Genetic Analysismentioning
confidence: 99%